2023
DOI: 10.1126/sciadv.ade6415
|View full text |Cite
|
Sign up to set email alerts
|

Rapid topographic growth of the Taiwan orogen since ~1.3–1.5 Ma

Abstract: We present the first paleotopographic reconstruction of Taiwan by measuring the hydrogen isotope composition of leaf waxes (δ 2 H n C29 ) preserved in 3-Ma and younger sediments of the southern Coastal Range. Plant leaf waxes record the δ 2 H of precipitation during formation, which is related to elevation. Leaf waxes produced across the orogen are transported and deposited in adjacent sedimentary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
(126 reference statements)
0
0
0
Order By: Relevance
“…Metamorphism increases from west to east across the Taiwanese ranges due to the immense amount of compression from the Philippine Sea Plate. Huang et al (2015) and Chang et al (2023) indicated that the Central Range is rising at 1 cm/year and that much of the past orogenic activity occurred between 1.5-1.3 My and 300 Ka, while uplift rates for the Coast Range are more muted and range from 2 mm/year in the south to 5 mm/year in the north. Indeed, the metamorphosed marble formations at Taroko Gorge depicted in Figure 2a, with their compressed and contorted appearance derived from this tectonic setting, combined with a distinct series of ecological zones (discussed later), form an important baseline for its national park status and its role as a magnet for tourism.…”
Section: Landformsmentioning
confidence: 99%
“…Metamorphism increases from west to east across the Taiwanese ranges due to the immense amount of compression from the Philippine Sea Plate. Huang et al (2015) and Chang et al (2023) indicated that the Central Range is rising at 1 cm/year and that much of the past orogenic activity occurred between 1.5-1.3 My and 300 Ka, while uplift rates for the Coast Range are more muted and range from 2 mm/year in the south to 5 mm/year in the north. Indeed, the metamorphosed marble formations at Taroko Gorge depicted in Figure 2a, with their compressed and contorted appearance derived from this tectonic setting, combined with a distinct series of ecological zones (discussed later), form an important baseline for its national park status and its role as a magnet for tourism.…”
Section: Landformsmentioning
confidence: 99%
“…In contrast, locally sourced organic matter may capture environmental signals over years to thousands of years, representing much smaller spatial scales. Chang et al, 2023) In young floodplain surfaces or channels, the organic carbon is mainly detrital, derived from various parts of the upstream catchment area. Conversely, mature floodplain surfaces, which remain stable long enough to develop soils, accumulate significant amounts of in situ organic carbon that contains local environmental signals (Bobik, 2021).…”
Section: Quantitative Constraints On Catchment Reliefmentioning
confidence: 99%